Empowerment of msmes resilience with pestel the strategy to minimize economic poverty in East Nusa Tenggara province - Enike Tje Yustin Dima Dima; Maria Augustin Lopes Amaral; Beatrix Yunarti Manehat (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the relationship between Political, Economic, Social, Technological, and Environmental (PESTEL) factors with the MSME resilience variable to minimize economic poverty in East Nusa Tenggara Province. Research using quantitative research methods. Data was taken by distributing questionnaires to 231 food SMEs in Kupang City. The sample selection used the covinience sampling method.Data analysis using PLS SEM and the results of the study show that political and technological factors have no effect on MSME food security and do not minimize economic poverty in Kupang City. The ineffectiveness of these two factors on the resilience of MSMEs is because the Kupang City government does not yet have regulations regarding MSME empowerment. For technological factors, MSME marketing in Kupang City still relies on the Word of Mouth model rather than the use of technology.On the other hand, economic, social and environmental factors influence the resilience of food MSMEs and are able to minimize economic poverty in Kupang City, NTT Province. Changes in the lifestyle of the people in Kupang City as part of social factors, increased economic activity in the community, and integrated aspects of community life as indicators of environmental aspects support the resilience of MSMEs and minimize poverty in the Province of NTT.